Prognozirovanie sportivnych dostiženij u grebcov-kanoistov vysšej kvalifikacii s pozicii skorosti ich postnagruzocnogo vosstanovlenija - Makarova, G. A.; Chernukha, S. M.; Karpov, A. A.; Bushueva, T. V.; Baranovskaya, I. B. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
Aim: to investigate the afterload recovery rate of some biochemical and physiological parameters as well as criteria of psycho-emotional state in the context of forecasting level and stability of athletic achievements in 19 highly trained male canoeists aged from 21 to 33 years. The studies were performed repeatedly (25 to 40 times) within a span of 3 years. The registered parameters: contents of hemoglobin, iron, alanine aminotransferase, aspartate aminotransferase, total creatine phosphokinase, urea, cortisol, total testosterone, free testosterone, total protein, hematocrit volume, results of questionnaire survey (sleep, appetite, motivation to train), heart rate, systolic and diastolic blood pressure; pulse pressure and double product were calculated. Integrated index of functional state (Omega hardware-software complex) and parameters of examination using Kardiovisor program module has been determined. Data record protocol: 14 hours after the last training at the beginning and at the end of a week-long micro cycle, 20 hours after the last training at the end of a week-long micro cycle and after 44 hours of rest since the last training. Receiver Operating Characteristic (ROC) analysis was applied for appraisal of the findings. Results; Only high tolerance of central nervous system`s functional state, its psychoemotional component in particular (motivation to train, sleep, appetite), to exercise-induced metabolic shift and higher cortisol level in blood at the end of a week-long micro cycles serve as prognostically significant parameters for classification into "successful" subgroup regarding the level and stability of athletic achievements in highly trained canoeists.